Fenomena Alih Kode dan Campur Kode pada Percakapan Santriwati di Markaz Al-'Arabiyah Al-Ittifaqiah - Ulfa Hoyriah; Novia Ulfa Safitri; Sabina Evariyani (Lingua Franca, 2025)
Language is the main tool in the human communication process, both in the formal and informal realms. In a multilingual society, the use of language is often not limited to just one language, but involves more than one language in a single speech event. This condition gives birth to various linguistic phenomena, one of which is code switching and code mixing, which often appear in daily interactions.  Markaz Al Arabiyah Al-Ittifaqiah as an institution that emphasizes the use of Arabic in daily life becomes an interesting social space to observe this phenomenon. In the conversation of students, it is often found that the use of two or more languages alternately or simultaneously is found. This study aims to analyze the phenomenon of code switching and code mixing in the conversations of female students at Markaz Al Arabiyah Al-Ittifaqiah Indralaya. This study uses a qualitative approach with observation, interview, and documentation methods to identify forms of code switching and code mixing and the factors that influence them. The results of the study showed that the code switching that occurred in the Markaz Al Arabiyah environment was an external code transfer (Arabic, Indonesian, local language, and English), while the code mixing that occurred was in the form of the insertion of word elements, phrases, basters, repetitions of words, expressions, or inserts, as well as sentence levels into the main language (Arabic). Factors that affect the occurrence of code switching include: Speaker Factors, Communicator Factors, and Third-Party Factors. At the same time, code switching is influenced by the similarity of native language background, limited vocabulary, adaptation factors, and the habits and manners of the speaker. This phenomenon reflects the bilingualism of students in Arabic and is a challenge in the implementation of Arabic language policies in the educational environment. This research is expected to contribute to sociolinguistic development, especially in the context of Arabic language education in Indonesia.